Diagnostic efficacy of bronchoalveolar lavage (BAL) in lung malignancies - Tayal, Shubhra; Bhale, Chandrashekhar P. (International Journal of Research in Medical Sciences, 2018)
Background: Lung malignancies are the leading cause of cancer related deaths in men and in women it has surpassed even breast cancer. With the development of flexible fiber-optic bronchoscope, respiratory cytology has newer approach as samples like bronchial washings, bronchial brushings, bronchoalveolar lavage and trans-bronchial needle aspirations could be collected from the respiratory tract, yielding significant amount of cytological material. Methods: A prospective study conducted in department of pathology in MGM Medical College and Hospital, Aurangabad during a period from November 2015 to October 2017. 48samples of bronchoalveolar lavage received and patient data collected. Results: About 48 cases included in the study comprised of 23 (47.92%) malignancies, 16 (33.34%) DLDs and 9 (18%) cases of tuberculosis. In our study, 23 cases of malignancy included 15 male and 8 female patients (male:female ratio= 1.87). Mean age for malignancy was 57.57 years with median age of 60 years. Among 23 cases of malignancies 11 were given as positive/suspicious/atypical cells on BAL, whereas 10 out of 11 bronchial brushing were given as positive/suspicious or suggestive of malignancy. Conclusions: Bronchoalveolar lavage is useful procedure. Efficacy of BAL is increased when used in combination with bronchial brushing.